Archetypal life themes, career orientations, and employability satisfaction of higher education students: a postmodern career counselling perspective - Coetzee, Melinde (South African Journal of Higher Education, 2016)
The objective of the study was to explore the constructs archetypal life themes (measured by the Pearson-Marr Archetype Indicator), and career orientations (measured by the Career Orientations Inventory) from a postmodern career counselling perspective in facilitating students’ employability satisfaction (measured by a single item scale). A random sample of 270 predominantly black and female distance learning undergraduate students (mean age = 32) employed in the service industry participated in the survey. Correlational statistics revealed statistically significant relationships between the participants’ current active archetypal life themes, their dominant career orientations and employability satisfaction. The value of the findings lies in the explanatory utility of the identified empirical relationships between the three variables in postmodern constructivist and narrative career counselling approaches interested in combining facets of quantitative with qualitative assessments. Keywords: archetypes, life themes, career counselling, career anchors, career orientations, employability satisfaction